226 Temporal Variation in Consent Litigation in General Surgery. (19th August 2022) - Sebastian, A; Wyld, L; Morgan, J
Abstract: Aim: Issues with consent is one of the most common causes of litigation within General surgery. The guidance surrounding informed consent in surgery has changed following the Montgomery vs Lanarkshire Health Board (2015) court ruling. The aim of this study was to examine the time trends in medico-legal cases related to consent between 2011–2020. Method: Data on the numbers of litigation cases in general surgery were obtained from NHS resolutions for the period of 2010–2020. Chi-squared analysis was performed using SPSS to compare the proportion of litigation cases that were due to consent before and after 2015. Results: There were a total of 10, 027 general surgery claims made between 2010–2020, of which 580 (5.8%) were related to issues with consent. The number and proportion of claims related to consent rose during the study period, with 208/2817 (3.76%) consent-related cases before 2015, versus 372/3267 (8.12%) after 2015; a 116% increase (p<0.001). Conclusions: These data illustrate a significant rise in medico-legal claims related to consent in General surgery in the post-Montgomery era. This may be due to legal precedent being established following the Montgomery case, and the increased awareness of these issues as a result.